POTENSI ARTIFICIAL INTELLIGENCE (AI) MENERBITKAN OPINI AUDITOR ? - Soeprajitno, Raden Roro Widya Ningtyas (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2019)
The presence of Artificial Intelligence (AI) in the disruptive era is considered to be a solution for the inability of the audit to detect fraud and issue an audit opinion. The purpose of this study is to prove the potential of Artificial Intelligence (AI) to detect fraud and issue auditor opinion. This study uses the Theoretical Framework method and uses documentation techniques for previous research and by combining competencies and capabilities between the availability of big data, the use of data mining, Artificial Neural Network and involving the final analysis through the calculation of total irregularities obtained by using Fuzzy. The results of this paper reinforce the potential for the existence of Artificial Intelligence to be able to detect fraud, and publish audit opinions independently. The author hopes to provide a broader picture of the Artificial Intelligence framework to maximize its potential to help auditors detect and issue audit opinions.